A very rare mass in the uterus: Malignant lymphoma - Fatma Devran Bıldırcın (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2019)
The female genital area is the fi rst site of malignant lymphoma; is a very rare localization.While most genital lymphomas occur in the vagina or cervix, uterine corpus is very rare [1]. Patients usually present with bleeding or pelvic, low back pain, but very rarely tumors are discovered through a routine examination. In the present case; When the radiological examination was performed for avascular femoral necrosis, it was thought that myoma was the incidental mass. However, the patient had no preoperative diagnosis and the pathology was high grade B-cell lymphoma located in the uterus. We were unable to make a preoperative diagnosis and we thought that it could be lyomyosarcoma. Here we report a case of primary lymphoma of the uterus, which is very rare among postmenopausal masses.